Studi Literatur Pemanfaatan Tanaman Suku Zingiberceae sebagai Antidepresan - Afifah, Aminia; Kurniadi, Dede; Nurul; Wardani, Diah (Jurnal Medika Farmaka, 2023)
Introduction: Depression is a mental disorder characterized by persistent depressed feelings that can affect mood, behavior and physical health. Based on basic health research data in 2018, the total number of cases affected by depression in Indonesia at the age of more than 15 years reached 6.1%. Depression therapy generally uses antidepressant drugs. The side effects of antidepressant drugs are not light, therefore it is necessary to explore plant-based medicine to treat mental disorders. Therefore, to avoid the side effects caused by these antidepressant drugs, alternative medicine from plants can be used. One of the plants that have the potential as an antidepressant is from the Zingiberaceae family. Method: The method used in writing is by conducting a literature study related to plants of the Zingiberaceae family which have the potential to have antidepressant activity contained in national and international journals published in the last 10 years. Result: Based on the results of literature research, there are several plants that have potential as antidepressants, there are 5 plants from the Zingiberaceae family, including Turmeric (Curcuma longa L), Temulawak (Curcuma xanthoriza), Temugiring (Curcuma heyneana), Black turmeric (Curcuma caseia) and the last namely Ginger (Zingiber officinale Rosc). Plants that have the greatest antidepressant activity are Curcuma heyneana plants with doses of 100 and 200 mg/kg. Conclusion. With the preparation of this paper, it is hoped that it can provide scientific information about plants that have the potential as antidepressants derived from plants of the Zingiberaceae family which can be used as an alternative treatment for depression mental illness.